Efeito do tamanho de cristalito no sensor de campo magnético baseado no interferômetro de Mach-Zehnder com nanopartículas - Araújo, Matheus Rodrigues (2021)
In this work, the effect of crystallite size in a Mach-Zehnder interferometer on optical fibers was studied by coating one of the sensor arms with nanoparticles. In the interferometer, an optical signal is divided into two signals, one for the sensor fiber, coated with nanoparticles, and the other for the reference fiber. The vibration of nanoparticles in the presence of a magnetic field alters the sensor transmission causing an imbalance between the optical signals of the interferometer arms. The nanoparticles used were nickel ferrites (NiFe2O4) with mean crystallite sizes of 3.3 nm, 51.9 nm and 74.3 nm. The protein sol-gel method was used to obtain nickel ferrite as it allows good control of the nanostructure characteristics, especially the size of the crystallites. The nanoparticles were characterized by X-ray fluorescence, X-ray diffraction, VSM magnetic measurements and Mössbauer spectroscopy. The structural parameters extracted from X-ray diffraction were refined by the Rietveld method. The average size of crystallites was determined by the Scherrer equation and by the graphic methods of Williamson-Hall and Size Strain Plot, from the values of the width at half height of the diffraction peaks (FWHM – Full Width at Half Maximum); by the graphic methods of Williamson-Hall and Size Strain Plot, the microdeformation was determined. The performance of the magnetic sensor was analyzed in relation to the parameters of sensitivity, precision and accuracy for different sizes of nanoparticles. It was observed that the relationship between the output power and the applied magnetic field presented linearity between 87.6% and 99.2%. The sensitivity for the different particle sizes ranged between 1.31 dB/mT and 2.49 dB/mT, showing that the sensor sensitivity increases with the magnetization of the nanoparticle.